Cryptococcosis gattii: A literature review (Research, Society and Development, 2025)
Introduction: Cryptococcus gattii causes an invasive fungal infection with a high morbidity and mortality rate. Its prevalence is estimated at 11% to 33% of cryptococcosis cases globally, and it can affect both immunocompetent and immunosuppressed patients. This article aims to present a review of Cryptococcosis gattii. Method: This study consists of a literature review of articles found in the indexing platforms PubMed and Scielo, published in the last 15 years. All selected articles answered the guiding question and passed the inclusion and exclusion criteria. Results and Discussion: C. gattii is widely found in wooded regions and has been isolated from house dust in the Amazon. Although most studies show that the disease affects immunocompetent patients, recent evidence points to potential genetic and immunological factors predisposing to infection. The pathogen is typically acquired through the respiratory tract, with the lungs being the organ initially affected. Mortality and sequelae of central nervous system cryptococcosis due to C. gattii remain high. Conclusion: C. gattii is a highly prevalent pathogen with significant case fatality rates. This pathology should always be considered in the differential diagnosis of patients with chronic pulmonary conditions, regardless of their level of immunocompetence. Studies considering new therapeutic regimens are encouraged.